Phenotypic antimicrobial susceptibility testing of Chlamydia trachomatis isolates from patients with persistent or successfully treated infections. (30th November 2017) - Pitt, Rachel; Alexander, Sarah; Ison, Catherine; Horner, Patrick; Hathorn, Emma; Goold, Penny; Woodford, Neil; Cole, Michelle J
Abstract: Objectives: Antimicrobial susceptibility data for Chlamydia trachomatis are lacking. Methodologies for susceptibility testing in C. trachomatis are not well-defined, standardized or performed routinely owing to its intracellular growth requirements. We sought to develop an assay for the in vitro susceptibility testing of C. trachomatis isolates from two patient cohorts with different clinical outcomes. Methods: Twenty-four clinical isolates (11 from persistently infected and 13 from successfully treated patients) were overlaid with media containing two-fold serial dilutions of azithromycin or doxycycline. After incubation, aliquots were removed from the stock inoculum (SI) and each antimicrobial concentration for total RNA extraction, complementary DNA generation and real-time PCR. The MIC was defined as the lowest antimicrobial concentration where a 95% reduction in transcription was evident in comparison with the SI for each isolate. Results: MICs of azithromycin were comparable for isolates from the two patient groups (82% ≤ 0.25 mg/L for persistently infected and 100% ≤ 0.25 mg/L for successfully treated patients). Doxycycline MICs were at least two-fold lower for isolates from the successfully treated patients (53.9% ≤ 0.064 mg/L) than for the persistently infected patients (100% ≥ 0.125 mg/L) ( P = 0.006, Fisher's exact test). Overall, 96% of isolates gave reproducible MICs when re-tested. Conclusions: A reproducible assay was developed for antimicrobial susceptibility testing of C. trachomatis . MICs of azithromycin were generally comparable for the two different patient groups. MICs of doxycycline were significantly higher in the persistently infected patients. However, interpretation of elevated MICs in C. trachomatis is extremely challenging in the absence of breakpoints, or wild-type and treatment failure MIC distribution data.